Respostas

2013-07-16T21:48:40-03:00
Desenvolvendo fica x²+6x+8=0 Aplicando bhaskara  
X=-6+-raizde(6²-4*1*8)/2*1
X=-6+-raiz de 36-32/2
X=-6+-raiz de 4/2
X=-6+-2/2
X'=-6+2/2 = -4/2 = x'=-2
X"=-6-2/2 = -8/2 = x"=-4
S={-2,-4)
2013-07-16T22:14:27-03:00
(x+1).(x-2)= -7x-10
x² - 2x + x - 2 = - 7x - 10
x² - x - 2 + 7x + 10 = 0
x² + 6x + 8 = 0
então: a=1  b=6   c= 8
aplicando bascara ...... [-b+-raiz quadr. de (b² - 4*a*c)] / 2*a
[-6+- raiz quadr.de (6²-4*1*8)]  /  2*1
[-6 +- raiz quadr. (36 - 32) ] / 2
[-6 +- raiz quadr.(4) ] / 2
[-6 +- raiz quadr. (2²) ] / 2
[-6 +- 2] / 2
x1= (-6 +2) / 2 ..... -4 / 2 .....-2
x2= (-6 -2) / 2 ...... -8 / 2 .... -4

{-2;-4}